The book of turtles - Montgomery, Sy (Clarion Books, an imprint of HarperCollins Publishers, 2023)
"This tribute to one of the most diverse, fascinating, and beloved species on the planet (turtles) speaks to the diversity and wisdom of these long-lived reptiles"--